Perceptions on the Quality of Life of Caregivers Caring for Older Adults With Alzheimer's Disease in Brazil: An Urgent Need for Social (International Journal of Studies in Nursing, 2020)
The aim of this research was to analyze the perceptions on the quality of life of caregivers who care for older adults with Alzheimer's disease. This study was conducted in the municipality of Betim, located in the metropolitan area of Belo Horizonte, Brazil. Thirty-two interviews were conducted with formal and informal caregivers. Data were organized into two empirical categories which affect the quality of life of caregivers: 1) older adult’s familial support, and 2) the burden of caregiver’s extensive workload. Results indicate that the quality of life of a caregiver can be elevated and improved through social support services provided by healthcare professionals, as well as health and social policies which allow a stronger support of caregivers through governmental programs.